Effectiveness of an Electronic Performance Support System on Computer Ethics and Ethical Decision-Making Education - Kert, Serhat Bahachr; Uz, Cigdem; Gecii, Zeynep (INT FORUM EDUCATIONAL TECHNOLOGY & SOC, NATL TAIWAN NORMAL UNIV, 2014)
This study examined the effectiveness of an electronic performance support system (EPSS) on computer ethics education and the ethical decision-making processes. There were five different phases to this ten month study: (1) Writing computer ethics scenarios, (2) Designing a decision-making framework (3) Developing EPSS software (4) Using EPSS in a case-based computer ethics education process (5) Analyzing all of the data collected from the implementation. A total of 15 computer ethics scenarios were written by the researchers and revised in accordance with the opinions of 12 experts from different universities. Barger's (2008) ethical decision-making model was adapted to a flow chart for generating a decision-making framework for the system. Quantitative and qualitative research methods, multivariate analysis of variance and semi-structured interviews were used together to investigate the effectiveness of the system. The results showed that the EPSS that was developed improved the decision-making skills of the students in the experimental group who were faced with different computer ethics scenarios during the implementation of the study. To present a balanced view both positive and negative comments made by the students regarding the EPSS were recorded and are presented in the study.
Keywords: Media in education; Interactive learning environments; Pedagogical issues; Higher education; Computer ethics; ISSUES; MODEL; Education & Educational Research